A bibliometric study of scientific literature in Scopus on botanicals for treatment of androgenetic alopecia. (26th November 2015) - Rondanelli, Mariangela; Perna, Simone; Peroni, Gabriella; Guido, Davide
Summary: Background: In androgenetic alopecia, a number of botanicals are available that can effectively slow or reduce hair loss and inflammation or stimulate partial hair regrowth. The aim of this study was to provide a descriptive overview of the impact and production of literature on botanicals used for androgenetic alopecia and to perform a citation analysis of the related research articles. Methods: We searched for "alopecia" OR "androgenetic alopecia" OR "hair loss" AND "Camelia sinensis" OR (and other 15 botanicals) in ARTICLE (Title/Abstract/Keyword) in Scopus database. Results: A total of 29 references, that is, research articles, were retrieved by SCOPUS search, and 93.1% had been published since 2000. The majority (48.3%) describe applications of hair grow stimulants, followed by inhibitors of 5‐alpha‐reductase applications (27.6%), and studies concerning inhibitors of inflammation (24.1%). The citation analysis revealed a growing interest for this topic and the papers on hair grow stimulants are most cited. Citation trend of inhibition of 5‐alpha‐reductase articles is growing in the last years. Conclusions: This study has highlighted three important aspects: (1) growing interest for this topic; (2) evidences mainly in hair grow stimulants and recently in the inhibition of 5‐alpha‐reductase, as demonstrated by article and citation counts across years; (3) in addition, all major studies have been focused on green tea epigallocatechin‐3‐gallate, Serenoa repens, Citrullus colocynthis and Cuscuta reflexa.